2017
DOI: 10.1371/journal.pone.0183074
|View full text |Cite
|
Sign up to set email alerts
|

Short-term spheroid culture of primary colorectal cancer cells as an in vitro model for personalizing cancer medicine

Abstract: Chemotherapy treatment of cancer remains a challenge due to the molecular and functional heterogeneity displayed by tumours originating from the same cell type. The pronounced heterogeneity makes it difficult for oncologists to devise an effective therapeutic strategy for the patient. One approach for increasing treatment efficacy is to test the chemosensitivity of cancer cells obtained from the patient’s tumour. 3D culture represents a promising method for modelling patient tumours in vitro. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 55 publications
1
53
0
3
Order By: Relevance
“…Tumoroids were cultured based on the work by Jeppesen et al Tumour specimens were cut into 1‐2 mm 2 fragments using an ordinary scalpel while keeping the tissue on ice. Tumour fragments were washed with cold DPBS and dissociated partially by 1 mg/mL collagenase type II (Thermo Fisher Scientific) in DPBS at 37°C in several steps.…”
Section: Methodsmentioning
confidence: 99%
“…Tumoroids were cultured based on the work by Jeppesen et al Tumour specimens were cut into 1‐2 mm 2 fragments using an ordinary scalpel while keeping the tissue on ice. Tumour fragments were washed with cold DPBS and dissociated partially by 1 mg/mL collagenase type II (Thermo Fisher Scientific) in DPBS at 37°C in several steps.…”
Section: Methodsmentioning
confidence: 99%
“…Jeppesen et al. successfully formed spheroids from cells obtained from 15 of total 18 patients (83% success rate) with colorectal cancer in Petri dishes coated with agarose . Obtained spheroids consisted mostly of epithelial cells with up to 5% of fibroblast contamination and closely represented original tumor in terms of morphology and protein expression patterns ( Figure 5a).…”
Section: Dsrt On 3d Cell Culture Modelsmentioning
confidence: 99%
“…Authors observed distinct patterns of dose‐response in spheroids obtained from five different donors indicating maintenance of individual drug sensitivity profiles in spheroids during culturing period. Correlation of DSRT results with clinical outcome was not discussed . Hagemann et al.…”
Section: Dsrt On 3d Cell Culture Modelsmentioning
confidence: 99%
See 2 more Smart Citations